Smartphone-based dispatch of community first responders to out-of-hospital cardiac arrest - statements from an international consensus conference - Metelmann, Camilla (Scand J Trauma Resusc Emerg Med, 2021)
BACKGROUND: Over the past decade Smartphone-based activation (SBA) of Community First Responders (CFR) to out-of-hospital cardiac arrests (OHCA) has gained much attention and popularity throughout Europe. Various programmes have been established, and interestingly there are considerable differences in technology, responder spectrum and the degree of integration into the prehospital emergency services. It is unclear whether these dissimilarities affect outcome. This paper reviews the current state in five European countries, reveals similarities and controversies, and presents consensus statements generated in an international conference with the intention to support public decision making on future strategies for SBA of CFR. METHODS: In a consensus conference a three-step approach was used: (i) presentation of current research from five European countries; (ii) workshops discussing evidence amongst the audience to generate consensus statements; (iii) anonymous real-time voting applying the modified RAND-UCLA Appropriateness method to adopt or reject the statements. The consensus panel aimed to represent all stakeholders involved in this topic. RESULTS: While 21 of 25 generated statements gained approval, consensus was only found for 5 of them. One statement was rejected but without consensus. Members of the consensus conference confirmed that CFR save lives. They further acknowledged the crucial role of emergency medical control centres and called for nationwide strategies. CONCLUSIONS: Members of the consensus conference acknowledged that smartphone-based activation of CFR to OHCA saves lives. The statements generated by the consensus conference may assist the public, healthcare services and governments to utilise these systems to their full potential, and direct the research community towards fields that still need to be addressed. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s13049-021-00841-1.